Genetic Variants Assessing Crohn's Disease Pattern in Pediatric Inflammatory Bowel Disease Patients by a Clinical Exome Survey. Issue 15 (December 2021) - Noel, Dago Dougba; Marinella, Pinelli; Mauro, Giacomelli; Tripodi, Serena Ilaria; Pin, Alessia; Serena, Arrigo; Matteo, Bramuzzo; Giuseppe, Fuoti Maurizio; Patrizia, Alvisi; Stefano, Calza; Tommasini, Alberto; Raffaele, Badolato
Background: Inflammatory bowel diseases (IBDs) are complex, multifactorial disorders that comprise Crohn's disease (CD) and ulcerative colitis (UC). Recent discoveries have brought much attention to the genetic predisposition of patients with IBD. Here we evaluate the interaction between IBD genetic risk factors susceptibility and CD occurrence in an IBD pediatric patient population, performing a clinical exome survey. Methods: From February 2018 to April 2019, we collected blood samples from 7 pediatric patients with IBD concerns from several collaborating health centers and/or hospitals. Blood samples were processed by extracting and sequencing DNA for a clinical exome survey. Shophia-DDM-v3-4 platform allowed sequenced reads alignment on hg19 genome as well as genetic variant calling. Both IBD risk and pathogenic genetic variants covered by at least 20 reads were selected for subjacent analysis. Results: Normality and Bartlett tests of both risk and pathogenic genetic variants suggested random and heterogeneous distribution of these variants in this group of IBD pediatric patients. P value clustering analysis by processing 157 IBD risk factors revealed genetic heterogeneity in IBD population and suggested two pathways influencing IBD development. In particular, (1) genetic variants associated with autoimmune and (2) metabolic diseases and CD risk factors (rs2066844 and rs2241880 single nucleotide polymorphism variants, respectively, of genes NOD2 and ATG16L) were identified in distinct clusters of IBD patients ( P  < .05). Moreover, the heterogeneous distribution of the following variants rs10065172 (IRGM), rs1805010 (IL4R), rs5030737 (MBL2), and rs33995883 (LRRK2) in this group of IBD patients was consistent with their random distribution in that population. Conclusion: Our study revealed specific genetic variants linked to CD susceptibility, autoimmune and/or innate immunodeficiency as well as to metabolic defects, as favoring factors of IBD, suggesting the valuable role of next generation sequencing (NGS) approaches in IBD molecular diagnostic procedures.